The Development of Muslim Family Outfits from Batik Fabric - Banlengloi, Waraporn; Mauseng, Suwaybah; Chepo, Coliya (Journal of Home Economics Technology and Innovation, 2022)
The objectives of this research were to design and make Muslim family outfits from Batik fabric. This satisfaction surveyof consumers for Muslim family outfits made from batik used purposive sampling of 100 who were interested in batik cloth. The research tool was a questionnaire and the data was analyzed using frequency, percentage, and mean The results of this research were on the design and sewing of Muslim family the outfits were 5 prototype sets. It was that most of the respondents were female, aged 21-30 years. Most of the respondents knew about batik fabrics, studied about batik and sawing method of making batik fabrics. Most of the respondents were fond of the pattern of the and colors of batik fabrics. Most of them who love batik which accounted for 90 percent. The results of the research on the satisfaction with the design and sewing of Muslim family outfits from 5 prototype sets found that the overall satisfaction with the Muslim family outfits was at the highest level of satisfaction in terms of aesthetics, with an average of 4.60, followed by refinement in tailoring with an average of 4.59, followed by technical and decorative methods with an average of 4.49, and usability with an average of 4.45. All criterias were most satisfied